PENINGKATAN KEMAMPUAN LITERASI NUMERASI SISWA PADA MATEMATIKAMELALUI PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) - Antonius KAP Simbolon (Nusantara Hasana Journal, 2023)
Mathematics learning does not only focus on improving numeracy skills, because in reality numeracy skills are not enough to face everyday life problems. The demands on students' abilities to master mathematics include the ability to use numbers, mathematical symbols and arithmetic operation skills. This ability is related to numeracy literacy. This research aims to improve numeracy literacy skills in mathematics subjects with the Indonesian Realistic Mathematics Education Approach (PMRI) in class X students at Nur Azizi Private Vocational School, Tanjung Morawa. This research used a qualitative approach with a classroom action research design. The research was carried out in 3 cycles and involved 30 class X students. Data was obtained using observation, written tests and interviews. The results of the research show that the PMRI approach can improve numeracy literacy skills in mathematics subjects in class 47.58% in the inappropriate category, cycle II 63.45% in the inappropriate category, and cycle III 82.15% in the appropriate category. In teaching and learning activities, teachers are expected to use this method as an alternative in mathematics and other subjects to increase students' numeracy literacy activities and abilities and it is hoped that this research can be used as a reference for other researchers.